Acute Stroke in northern Portugal: outcomes and characteristics of patients in a Medical-Surgical Emergency Department - Sandra Domingues; Tiago Barros; João Correia; Arlindo Cruz; Nuno Araújo; Liliana Silva (Millenium)
Introduction: Stroke is a leading cause of morbidity and long-term disability worldwide, significantly impacting health systems and personal lives. Disparities in European access to stroke care suggest an increased burden on individuals and society. Effective management of acute stroke in emergency departments is critical, requiring a rapid and coordinated response to optimize clinical outcomes.